Digital Twins - An Explorative Case Study of Business Models - Klostermeier, Robin; Haag, Steffi; Benlian, Alexander (HMD : Praxis der Wirtschaftsinformatik, 2018)
Digital twins represent intelligent digital images of real products or pro- cesses. As innovative technology, digital twins offer great opportunities but also challenges for businesses which is why they are more and more important for prac- tice and research alike. In contrast to prior studies focusing on the technological perspective, this study applies a business modelling perspective and investigates digital twins in four explorative case studies of organizations differing in size and core activities. A comparative analysis based on the business model canvas shows great differences in the definition and business models of digital twins across cases resulting in substantial influences on the respective product range but also on all other business model components. All case organizations expect great opportunities for the business-to-business and in the medium-term, business-to-customer markets. The biggest challenges for the development and implementation of digitals twins are the lack of monetary incentives as well as interface problems. Implications for research and practice are provided.
Keywords: Digital twins; Digital business models; Digital transformation; Business Model Canvas; Opportunities; Challenges